Risk of Febrile Seizure Recurrence and Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The influence of febrile episodes, a risk factor for recurrence of febrile seizures, and outcome in 180 children followed prospectively after their first febrile seizure, were studied at the University of Oulu, Finland.